The Influence of Sea Surface Temperature Reemergence on Marine Stratiform Cloud. Issue 9 (9th May 2020) - Geiss, Andrew; Marchand, Roger; Thompson, LuAnne
Abstract: The global distribution of winter to winter sea surface temperature (SST) reemergence is analyzed using a novel metric based on an autoregressive 1 model, and the global impact of SST on cloud amount and cloud type are examined using satellite data. A region in the northeastern Pacific Ocean is identified where wintertime SSTs are correlated with the occurrence of marine stratiform cloud the following winter. This correlation is likely a manifestation of SST reemergence. We hypothesize that through this reemergence mechanism marine stratus cloud amount, and thus shortwave cloud radiative effect, in the northeastern Pacific exhibits memory on inter‐seasonal and even multi‐year time scales and that exploration of this relationship may provide insight into the SST—low cloud feedbacks. Plain Language Summary: Global satellite records of ocean temperature and cloudiness are compared, and one region in the North Pacific Ocean is identified where wintertime cloud amount is related to sea surface temperature from the prior winter. This is due to a combination of two well‐established effects: the strong link between low clouds and sea surface temperature, and sea surface temperature reemergence, a tendency for wintertime ocean temperatures to be influenced by ocean temperature from the previous winter. This relationship may be useful for understanding how cloud and sea surface temperature might interact in a changing climate. Key Points: Global patterns of SST reemergence and of cloud‐SST interaction are examined One region in the northeastern Pacific is identified where wintertime low cloud occurrence is correlated with the previous winter's SST